Evaluation and high temperature strengthening mechanism of alkali activated biological-ash hybrid glass fiber-carbon fiber cement slurry system - Zhang, Yihang; Wen, Jiaxin; Yin, Xuejiao (Frontiers in Energy Research, 2022)
In recent years, with the rapid development of biomass combustion power generation and heat generation as the main application industry, the amount of byproduct biological ash is also increasing year by year. How to effectively utilize the biological ash in a more green, environmental friendly and economic way has become a research hotspot. In view of the problem that the mechanical properties of the cement stone decreased when the conventional latex was used as the toughening agent, based on the introduction of high dispersive composite modified fiber to enhance the toughness of the cement stone, this paper analyzed the physical and chemical properties and application status of the biological ash, and further explored the influence and role of the biological ash as the cement stone admixture on the high-temperature mechanical properties of the composite fiber cement stone Mechanism. The results show that when the dosage of biological ash is in the range of 0–10% (wt%), it has little effect on the basic slurry properties of cement stone, and has a certain preventive effect on the gas channeling of cement stone. In the analysis of comprehensive mechanical properties, the activated biological ash can enhance the compactness of cement matrix under high temperature by reducing the Ca/Si ratio through the secondary pozzolanic effect, stimulate the formation of a large number of hydration products, and strengthen the later strength growth rate of cement. The high temperature resistance of cement paste can be effectively improved by hybrid high dispersion composite fiber.